Nanolantern-Based DNA Probe and Signal Amplifier for Tumor-Related Biomarker Detection in Living Cells - Wang, Dong-Xia; Wang, Jing; Cui, Yun-Xi; Wang, Ya-Xin; Tang, An-Na; Kong, De-Ming (Analytical chemistry (Washington), 2019)
The introduction of nanotechnology can overcome some inherent drawbacks of traditional DNA probes, thus promoting their applications in living cells. Herein, a three-dimensional DNA nanostructure, a DNA nanolantern, was prepared via simple nucleotide hybridization of four short-stranded oligonucleotides and successfully applied to the construction of a novel DNA probe and signal amplifier. Compared to most reported DNA nanostructures, a DNA nanolantern shows the distinct advantages of low cost, easy design and preparation, more and arbitrary adjusted probe numbers, and high fluorescence resonance energy transfer (FRET) signal readout. Compared to traditional DNA probes, the constructed nanolantern-based one has improved cell internalization efficiency, enhanced biostability, accelerated reaction kinetics, excellent biocompatibility, and greatly reduced false-positive output and was demonstrated to work well for probing the expression level of tumor-related mRNA and microRNA in living cells. The DNA nanolantern can also be easily integrated with some reported signal amplification strategies, e.g., isothermal hybridization chain reaction (HCR), and the obtained signal amplifier combines the advantages of the DNA nanolantern and the HCR, enabling sensitive imaging detection of ultralow abundance targets in living cells. This work demonstrated that this simple DNA nanostructure can not only improve the performance of traditional DNA probes but can also be easily integrated with reported DNA-based strategy and technology, thus showing a broad application prospect.